2021
DOI: 10.1002/ags3.12435
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the influence of pancreatic surgery on new‐onset and persistent diabetes mellitus

Abstract: Aim:The management of diabetes mellitus (DM) after pancreatic surgery is a longstanding issue. We aimed to investigate DM concerning pancreatic surgery, including new onset diabetes mellitus (NODM), DM resolution, and the change in insulin excretion before/after pancreatic surgery. Methods: We retrospectively investigated three different cohorts (total 403 patients) undergoing pancreatectomy. Of those, 275 patients without preoperative DM were investigated for the risk factors of NODM. Fifty-four patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…In a previous study, the remnant pancreatic volume was found to be a significant risk factor for DM, but this relationship was stronger in patients who underwent DP, rather than PD. 16 Another study showed that obstructive pancreatitis caused by periampullary PDAC exacerbates glucose intolerance by inhibiting insulin secretion and that treatment of the periampullary tumor by pancreatectomy sometimes permits the recovery of the function of the remnant pancreas by removing the obstruction. 17…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the remnant pancreatic volume was found to be a significant risk factor for DM, but this relationship was stronger in patients who underwent DP, rather than PD. 16 Another study showed that obstructive pancreatitis caused by periampullary PDAC exacerbates glucose intolerance by inhibiting insulin secretion and that treatment of the periampullary tumor by pancreatectomy sometimes permits the recovery of the function of the remnant pancreas by removing the obstruction. 17…”
Section: Discussionmentioning
confidence: 99%
“…A previous report suggested preoperative 24-hour urinary C-peptide excretion measurement and multiplication of this value by the predicted pancreatic volume as a predictor of postoperative endocrine function [11]. However, 24-hour urine storage is a complicated and burdensome test for patients and is considered less versatile.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, some studies examining factors contributing to the occurrence of NODM after pancreatectomy have reported contradictory findings [79]. However, only a few studies have evaluated the changes in endocrine function, particularly insulin secretion capacity, before and after pancreatectomy [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that between 10 and 60 percent of cysts, particularly intraductal papillary mucinous neoplasms (IPMN) and mucinous cystic neoplasms (MCN), have significant potential to develop into malignant cancer [ 10 , 11 , 12 , 13 ]. Patients presenting with likely mucinous cysts are candidates for surgical resection, which carries a 2–4% mortality risk, as well as a 21% risk of post-surgical new onset diabetes [ 14 , 15 ]. Disappointingly, surgical interventions are often performed for cysts that are later found to be benign, while patients with non-mucinous cysts could (if accurately classified) be spared costly long-term surveillance [ 14 ].…”
Section: Introductionmentioning
confidence: 99%